Community-Based Social Containment as a Strategy to Prevent The Coronavirus Disease (Covid-19) - Andi Nuriyanto; Laili Rahayuwati; Mamat Lukman (Journal of Nursing Care, 2021)
Various efforts have been made optimally in suppressing the upsurge number of the Coronavirus Disease (COVID-19) outbreak, but the incidence of confirmed cases continues to increase. Lack of understanding, awareness, and effective communication from the public in responding to the dangers and spread of COVID-19 requires the participation of the community to work together to create strategies to reduce the increase in confirmed cases. Research on community-based prevention of the spread of COVID-19 is still very minimal; more information is needed so that it can be the basis for determining new, more appropriate strategies. This article was written using a literature review method. The aim of this research is to find strategies to prevent the spread of COVID-19 at the community level. The entire article is a non-experimental study and is cross-sectional and observational from the Google Scholar, PubMed, and ERIC (EBSCO) database with a total of nine analysis articles originating from China, Australia, Italy, Indonesia and Saudi Arabia. Keywords used to determine articles are English "(coronavirus disease OR covid-19) AND (community empowerment) AND (prevention program) AND (community health)" and Indonesian "(coronavirus disease OR covid-19) AND (pemberdayaan masyarakat) AND (upaya pencegahan) AND (kesehatan masyarakat)". The results of this review provide an overview of new strategies that can be implemented in the form of the concept of Community-Based Social Containment (CBSC) with the principle of empowerment to accelerate the handling of the spread of COVID-19 at the community level. CBSC is implemented from, by, and for the community in coordinating, planning, monitoring, facilitating, and evaluating the performance of their areas. As a basis for evidance base practice, further research needs to be carried out related to the effectiveness of the implementation of the CBSC concept as concrete evidence that can be applied directly.